Double oxidation of D-xylose to D-glycero -pentos-2,3-diulose (2,3-diketo-D-xylose) by pyranose dehydrogenase from the mushroom Agaricus bisporus - Volc, J; Sedmera, P; Halada, P; Prikrylová, V; Haltrich, D (Carbohydrate research, 2000)
Pyranose dehydrogenase purified to homogeneity from the mycelia of the basidiomycete fungus Agaricus bisporus catalyzed the oxidation of D-xylose at C-2 to D-threo-pentos-2-ulose (2-keto-D-xylose) and successively at C-3 to D-glycero-pentos-2,3-diulose (2,3-diketo-D-xylose) using 1,4-benzoquinone as an electron acceptor. The sites of oxidation were deduced from the spectroscopic analysis (MS, NMR) of the N,N-diphenylhydrazone derivatives of the reaction products.
Keywords: xylosa; molekulární struktura; Hydrazones; hydrazony; Agaricus; Magnetic Resonance Spectroscopy; Xylose; oxidace-redukce; Ketones; Chromatography, High Pressure Liquid; Molecular Structure; ketony; Oxidation-Reduction; vysokoúčinná kapalinová chromatografie; karbohydrátdehydrogenasy; magnetická rezonanční spektroskopie; Carbohydrate Dehydrogenases